P137 Serum biomarkers of degradation and formation of type III, IV and V collagen are associated with disease activity in patients with Crohn's disease. (25th January 2019) - Domislovic, V; Mortensen, J H; Karsdal, M A; Barisic, A; Manon-Jensen, T; Krznaric, Z
Abstract: Background: Crohn's disease (CD) is characterised by episodes of relapse and remission and therefore requires continuous evaluation of disease activity. Extra Cellular Matrix (ECM) consists of basement membrane (BM) and interstitial matrix (IM). BM is positioned directly underneath the epithelial cells and consists mainly of type IV collagen, while IM consists mainly of type I, III and V collagen, and is produced by fibroblasts. Pathological environment, such as inflammation and fibrosis, leads to impaired remodelling, structure, quality and function of the collagen in the ECM. We investigated biomarkers of collagen degradation and formation and their association with disease activity and in patients with CD. Methods: In this cross-sectional study we measured five biomarkers of ECM remodelling in 75 patients with CD (60% males, age 35 (IQR 26.5–43.5)), and 29 healthy controls matched by age and gender. Biomarkers of type III collagen degradation (C3M) and formation (PRO-C3), type IV collagen degradation (C4M) and formation (PRO-C4) and type V collagen formation (PRO-C5) were measured in serum by ELISA. Inflammatory activity was defined as combination of clinical or biochemical activity (CDAI ≥150 or CRP >5). One-way ANOVA (Tukey's multiple comparisons test), and ROC analysis was applied in statistical analysis. Results: Biomarkers of interstitial matrix remodelling showed that C3M was significantly elevated in active CD compared with inactive CD ( p < 0.05) and HD ( p < 0.05), whereas PRO-C3 and PRO-C5 were significantly elevated in active CD and inactive CD compared with HD ( p < 0.001, p < 0.05)(Figure 1). Turnover type III collagen showed highest diagnostic accuracy for active disease (AUC=0.74). Area under curve was for C3M 0.63, PRO-C3 0.36 and PRO-C5 0.52. Biomarkers of BM remodelling showed significantly higher C4M in active CD compared inactive ( p < 0.05) and HD ( p < 0.001), whereas PRO-C4 was significantly elevated in active and inactive CD compared with HD ( p < 0.01). Area under curve was for C4M 0.64, C4M/PRO-C4 ratio 0.57 and PRO-C4 0.56. Depiction of type III, IV, and V collagen remodelling in CD, and differences between healthy donors, CD in remission and active CD. Conclusions: Both biomarkers of interstitial matrix (C3M) and basement membrane (C4M) were associated with disease activity. PRO-C3, PRO-C5 and PRO-C4 were associated with CD regardless of disease activity. Interstitial matrix biomarkers of turnover type III collagen C3M/PRO-C3 showed highest diagnostic accuracy for disease activity. In conclusion, these biomarkers may be used in monitoring and prediction of disease activity and in differentiation between patients with CD and healthy individuals.